Letter to Jane Tolmach from California Attorney General Stanley Mosk - Stanley Mosk:::::: (1961)
A letter to Jane Tolmach from California Attorney General, Stanley Mosk, that expresses his disdain of her entertaining right-wing ideas. Instead writes his own list of what he expects.